Effects of the COVID-19 pandemic on general health and malaria control in Ghana: a qualitative study with mothers and health care professionals - Heuschen, Anna-Katharina; Abdul-Mumin, Alhassan; Abubakari, Abdulai; Agbozo, Faith; Lu, Guangyu; Jahn, Albrecht; Müller, Olaf (Malaria journal, 2023)
COVID-19 has severely impacted health systems and the management of non-COVID-19 diseases, including malaria, globally. The pandemic has hit sub-Saharan Africa less than expected; even considering large underreporting, the direct COVID-19 burden was minor compared to the Global North. However, the indirect effects of the pandemic, e.g. on socio-economic inequality and health care systems, may have been more disruptive. Following a quantitative analysis from northern Ghana, which showed significant reductions in overall outpatient department visits and malaria cases during the first year of COVID-19, this qualitative study aims to provide further explanations to those quantitative findings.
Gesehen am 30.11.2023